Development of ESS scheduling algorithm to maximize the potential profitability of PV generation supplier in South Korea - Kong, Junhyuk; Jufri, Fauzan Hanif; Kang, Byung O.; Jung, Jaesung (Journal of Electrical Engineering and Technology, 2018)
Under the current policies and compensation rules in South Korea, Photovoltaic (PV) generation supplier can maximize the profit by combining PV generation with Energy Storage System (ESS). However, the existing operational strategy of ESS is not able to maximize the profit due to the limitation of ESS capacity. In this paper, new ESS scheduling algorithm is introduced by utilizing the System Marginal Price (SMP) and PV generation forecasting to maximize the profits of PV generation supplier. The proposed algorithm determines the charging time of ESS by ranking the charging schedule from low to high SMP when PV generation is more than enough to charge ESS. The discharging time of ESS is determined by ranking the discharging schedule from high to low SMP when ESS energy is not enough to maintain the discharging. To compensate forecasting error, the algorithm is updated every hour to apply the up-to-date information. The simulation is performed to verify the effectiveness of the proposed algorithm by using actual PV generation and ESS information.
Keywords: Day ahead market; Energy storage systems; Offer curve; Power producer; Progressive hedging method; Rolling horizon; Stochastic optimizations; Day-ahead market; Energy storage system; Multi-stage stochastic optimization; Offer curve; Progressive hedging method; Rolling horizon method; Wind power producers